MiR-145-5p regulates granulosa cell proliferation by targeting the SET gene in KGN cells - Gao LINGLING; Yang QINGXING; Xu JIANBO; Wang WEIJIE; Lu DAN (The Journal of Reproduction and Development)
MiR-145-5p has been implicated in the development and progression of various disorders, and it is primarily recognized as a tumor suppressor in numerous cancers types. Its expression has been reported to decrease in the granulosa cells of patients with polycystic ovarian syndrome (PCOS). This study aimed to investigate whether miR-145-5p plays a role in granulosa cell proliferation and to shed light on the underlying pathological mechanisms of follicular development in patients with PCOS. Follicular fluid samples were collected from patients with PCOS and healthy individuals. The Cell Counting Kit-8 and bromodeoxyuridine assays were performed to assess KGN cell proliferation. The expression of miR-145-5p was significantly decreased in PCOS granulosa cells than in control cells, whereas the expression of SET was increased. Furthermore, miR-145-5p suppressed the proliferation of KGN cells. SET was identified as a direct target of miR-145-5p. Additionally, SET promoted the proliferation of KGN cells, and knockdown of SET counteracted the effect of the miR-145-5p inhibitor. Therefore, miR-145-5p regulates granulosa cell proliferation by targeting the SET in KGN cells; this process may be a potential pathological pathway that contributes to follicular developmental disorders in PCOS.